Quantifying early stage irradiation damage from nanoindentation pop-in tests. (December 2018) - Jin, K.; Xia, Y.; Crespillo, M.; Xue, H.; Zhang, Y.; Gao, Y.F.; Bei, H.
Abstract: Early stage irradiation effects on incipient plasticity are quantitatively investigated in single-crystalline molybdenum using nanoindentation pop-in tests. Defects produced under low-dose ion irradiations, even when they are hardly detected by ion-channeling technique, can significantly reduce the critical stress for the elastic-plastic transition, through acting as heterogeneous dislocation nucleation sources. The density and strength of defects are derived using a unified model convoluting homogeneous and heterogeneous mechanisms. In addition to the increased defect density, defect strength is found to decrease with increasing irradiation dose, suggesting a growth in defect size, which is further evidenced by combined analyses between pop-in and hardness tests. Graphical abstract: Unlabelled Image